A Clinical Study on Axial Symptoms and Imaging Changes in Paraspinal Muscles after Cervical Posterior Open-door Laminoplasty - Yin, Hao; Han, Guang; Li, Qiang; He, Xuejun; Wang, Congyang (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
Objective This research aimed to gain a better understanding of the relationship between cervical posterior open-door laminoplasty on axial symptoms, the net cross-sectional area of paraspinal muscles, and the degree of pimelosis.Method A retrospective study was conducted on a consecutive series of 37 patients who had underwent cervical posterior open-door laminoplasty + lateral mass fixation and bone graft fusion between January 2015 and July 2015. All patients received postoperative examinations at 6 months and 18 months after the operation. For each follow-up visit, the VAS Rating Scale and ODI Function Index Questionnaire were filled out. Meanwhile, a C-Spine X-ray and MRI of the patients were taken. In the measurements taken with ImageJ 1.51 K Software, the cervical vertebra MRI T2-weighted image cross-section for each segment was measured separately, mainly including the mean T2 signal value of the contour area and the net area of the paraspinal muscles.Results Differences between VAS and ODI (%) at three different time points were of statistical significance (p < 0.01). Pairwise comparisons of the results showed that VAS and ODI (%) at different times were clearly different (p < 0.01). Differences in the mean T2 signal value and net area at different times were of statistical significance (p < 0.01). Pairwise comparisons of the results indicated that the mean T2 signal value and net area at different times were clearly different (p < 0.01). The corresponding analytical results for VAS, ODI (%), and the mean of the T2 signal value and net area demonstrated that VAS6 months after surgery was positively correlated to the net area of C3/4 and C4/5 (r = 0.352, p < 0.05; r = 0.338, p < 0.05). The analogous analytical results for the mean T2 signal value and net area were of no statistical significance (p > 0.05).Conclusions We believe that axial symptoms after cervical spine surgery does not affect the recovery of neurological function. There is a process of acute or subacute enlargement of paraspinal muscles on segments C3/4 and C4/5 after the operation, while the results of the follow-up visits show that there is a gradual process of atrophy in local posterior muscles, which may be related to axial symptoms. The degree of pimelosis of the neck paraspinal muscles may have no relationship with axial symptoms.
Keywords: open-door laminoplasty; axial symptoms; paraspinal muscles; imaging